2016
DOI: 10.26417/ejms.v1i2.p164-173
|View full text |Cite
|
Sign up to set email alerts
|

Does Enhancing of the Competitiveness Influence on Foreign Direct Investments in Western Balkan Countries?

Abstract: Foreign direct investments present a valuable source of national competitiveness as they have attributes of capital flows provide knowledge and technology transfer from one country to target country. In this paper are used variables defined by World Economic Forum which construct Global Competitiveness Index for assessing competitiveness of the country. The purpose of the research is to examine does the national competitiveness increase enhance the level of FDI flows in transition Western Balkan economies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
1
8
0
1
Order By: Relevance
“…Other studies showed that competitiveness is also very important factor for FDI in Central and Eastern European countries (Paul, Popovici, & Cǎlin, 2014;Popovici & Călin, 2012). Zlatković (2016) found very similar results with positive effects of each competitiveness pillar and FDI for the Balkan countries. Very extensive research in this field has been conducted by Curtis, Rhoades, & Griffin (2013).…”
Section: Literature Reviewsupporting
confidence: 57%
See 3 more Smart Citations
“…Other studies showed that competitiveness is also very important factor for FDI in Central and Eastern European countries (Paul, Popovici, & Cǎlin, 2014;Popovici & Călin, 2012). Zlatković (2016) found very similar results with positive effects of each competitiveness pillar and FDI for the Balkan countries. Very extensive research in this field has been conducted by Curtis, Rhoades, & Griffin (2013).…”
Section: Literature Reviewsupporting
confidence: 57%
“…Foreign direct investments are highly important for developing countries especially because they provide different benefits such as provision of capital or transfer of technology. Positive effects of global competitiveness on foreign direct investments is well-known fact from practice and confirmed by different empirical studies (Popovici & Călin, 2015;Anastassopoulos, 2007;Zlatković, 2016;Curtis, Rhoades, & Griffin, 2013). Anastassopoulos (2007), based on the sample of 15 EU member countries, found a positive effect between competitiveness and FDI inflows.…”
Section: Literature Reviewmentioning
confidence: 71%
See 2 more Smart Citations
“…Kordalska and Olczyk (2015) observe reverse causality between economic growth and competitiveness. Providing knowledge and technology transfer along with the attributes of capital inflows, FDI constitutes a valuable source of national competitiveness to the target country (Zlatcovic, 2016). Competitiveness revealed by costs and embedded technology can have significant effects on export market performance (Carlin et al , 2001).…”
Section: Introductionmentioning
confidence: 99%